The Justice in Islam: An Example of Qiṣāṣ Implementation in Islam - Muh. Syaifudin & Noor Achmad (TAWASUT, 2015)
AbstractThis research aims to present an objective description about Qisas (retaliation) in Islam as one of sensitive punishments in the Muslim and world society as well. It is as the impact of spreading globalization that popularizes human rights and liberalism. This study uses descriptive analytical method. It tries to uncover basic foundation of Islamic law and principles of Muslim interrelation. Punishment in Islam is only based on justice and maintenance broader social welfare. It could not be executed if just be based on the assumption and not the concrete passages. Moreover, there are so many requirements and principles that must be fulfilled to implement it. The interesting one is the prophetic tradition ordered to avoid giving the punishment as we can. Thus the implementation of law in Islam like qisas (retaliation) is hardly practiced. In other word, views on Islamic law should be clearly objective and uses various perspectives to reach scientific and objective conclusion. Keywords: Islam; justice, qiṣāṣ;punishment of crime